Variation of fundamental features of cobalt surface-layered Bi-2212 superconductor materials with diffusion annealing temperature - Oz, Ilker; Terzioglu, Cabir; Oz, Muhammed; Ulgen, Asaf Tolga; Turkoz, Mustafa Burak; Erdem, Umit; Yildirim, Gurcan (Elsevier Sci Ltd, 2023)
The present study appears extensively on the role of diffusion annealing temperature intervals 650-850 degrees C on electrical conductivity, flux pinning ability, superconducting and crystallinity quality of Cobalt (Co) surface -layered Bi-2212 compounds with experimental tests including dc resistivity, bulk density, X-ray diffraction, critical current density measurements, and theoretical calculations. Experimental findings display that the Co ions may be replaced mostly by bismuth sites in the crystal lattice as a consequence of appropriate cation -vacancy, electron configurations of the outer shell, chemical valence states, and electronegativity of chemical contents in the main composition. The fundamental characteristic features refine considerably with 650 degrees C annealing temperature due to enhancement of antiferromagnetic spin fluctuations in the clusters of micro -domains, re-ordering of Cu-O bonds, stabilization of system, pairing mechanism, modulation of insulating Bi-O double layers, and orbital hybridization mechanisms. Accordingly, bulk Bi-2212 ceramic obtained at optimum annealing temperature exhibits the best conductivity because of a decrease in systematic crystallinity problems and potential grain boundary interaction problems expected in the system. Likewise, the optimum annealing temperature triggers the artificial nucleation regions for 2D discrete pancakelike Abrikosov vortices to decelerate thermal fluxon movements. Moreover, the X-ray diffraction results indicate that optimum Co ions in crystal lattice significantly improve crystal structure quality, grain alignment distributions in c-axis orientation, the extension of high-Tc Bi-2223 superconducting phase, and average crystallite size parameters. Additionally, the nucleation activation energy is noticed to reduce with optimum Co ions due to enhancement in the nucleation stability and crystallization temperature values to higher temperature zones. Namely, optimum Co ions easily diffusing into the lattice points support the formation of surface nucleation. In contrast, after a critical value of 650 degrees C, the characteristic properties mentioned suppress remarkably. In conclusion, the main characteristic features are extensively improved by the optimum diffusion annealing temperature for usage in novel and feasible market areas.
Keywords: Bi-2212 crystal system; Diffusion; Crystallization stability; Pairing mechanism; Flux pinning ability